Daily Life Experiences of Working Women in Existential Threat - Şeker, Betül Dilara (Border Crossing, 2024)
The pandemic has profoundly impacted daily life, resources, and gender roles, resulting in significant changes. This study examines how the gender roles of working women transform in the face of existential threats. We investigate their experiences, reactions, and defense mechanisms during the pandemic. The sample consists of 17 women, revealing increased inequalities and responsibilities faced in both domestic and professional settings. Participants expressed uncertainty, anxiety, and fear for their loved ones, sharing experiences with the disease, preventive measures, and psychological and social consequences. Understanding the defense mechanisms used by women will bring short-term individual benefits. This research sheds light on women’s experiences during the pandemic, highlighting the urgency of addressing gender disparities in COVID-19.